Phubbing in Romantic Relationships: Cell Phone Use, Couple Satisfaction, Psychological Well-Being and Mental Health - González-Rivera, Juan (2018)
The purpose of this study was to evaluate if frequent cell phone use (phubbing) has a direct impact in the couple’s satisfaction, and an indirect effect on the psychological well-being and mental health of Puerto Rican. Study 1 examines the psychometric properties of the Partner Phubbing Scale and the Cell Phone Conflict Scale. The scales were found to be highly reliable and valid. Study 2 assessed the study’s proposed relationships among a non-probabilistic sample of 392 Puerto Ricans, selected by availability. The results showed a significant mediation of couple’s satisfaction in the relationship between phubbing, psychological well-being and mental health. Overall, participants who rated more phubbing in their relationships also reported lower couple’s satisfaction, more symptoms related to depression, anxiety and stress, and lower psychological well-being. Our study provides empirical evidence on the negative effect of excessive use of cell phones within romantic relationships, as well on people’s mental health.